2005
DOI: 10.1080/14756360500043257
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro antibacterial, antifungal and cytotoxic properties of sulfonamide—derived Schiff's bases and their metal complexes

Abstract: A series of new antibacterial and antifungal Schiff's bases derived from sulfonamides, as well as their transition metal complexes incorporating cobalt (II), copper (II), nickel (II) and zinc (II) were synthesized, characterized and screened for their in-vitro antibacterial activity against six Gram-negative (Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, Pseudomonas aeruginosa, Salmonella typhi and Shigella dysentriae) and four Gram-positive (Bacillus cereus, Corynebacterium diphtheriae, Staphylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(70 citation statements)
references
References 28 publications
(47 reference statements)
3
51
1
Order By: Relevance
“…Besides this many other factors such as solubility, dipole moment, conductivity influenced by metal ion may be possible reasons for the remarkable antibacterial activities of these complexes [42]. It has also been observed that some moieties such as the azomethine linkage or heteroaromatic nucleus introduced into such compounds exhibit extensive biological activities that may be a result of the increase in hydrophobic character and liposolubility of the molecules in crossing the cell membrane of the microorganism and enhance the biological utilization ratio and activity of complexes [43]. …”
Section: Discussionmentioning
confidence: 99%
“…Besides this many other factors such as solubility, dipole moment, conductivity influenced by metal ion may be possible reasons for the remarkable antibacterial activities of these complexes [42]. It has also been observed that some moieties such as the azomethine linkage or heteroaromatic nucleus introduced into such compounds exhibit extensive biological activities that may be a result of the increase in hydrophobic character and liposolubility of the molecules in crossing the cell membrane of the microorganism and enhance the biological utilization ratio and activity of complexes [43]. …”
Section: Discussionmentioning
confidence: 99%
“…The CO 2 -hydratase activity as an enzyme unit (EU) was calculated by using the equation ((t 0 _ t c )/t c ) where t 0 and t c were the times for pH change of the nonenzymatic and the enzymatic reactions, respectively. The IC 50 values (the concentration of inhibitor producing a 50% inhibition of CA activity) were obtained in vitro for the synthesised compounds (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), with 1 and 2 as the control compounds.…”
Section: Hydratase Activity Assaymentioning
confidence: 99%
“…Furthermore the sulphonamides are the best-known inhibitors of the carbonic anhydrase enzyme, currently used for the treatment of glaucoma in clinical medicine [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Schiff bases H 2 L 1 -HL 7 obtained from interaction of salicyl aldehydes and appropriate amine were used as tridentate ligands containing ONO, ONS or ONN as donor atoms (Figure 1). Diamine L 8 , H 4 EDTA and H 5 DTPA were also used as ligands. The composition and structure of synthesized complexes were analysed by elemental analysis, IR and NMR spectroscopies, magnetochemical, thermoanalytical and molar conductance measurements.…”
mentioning
confidence: 99%